MENOPAUSE DAN PENGARUHNYA DALAM KEHIDUPAN PERKAWINAN - Nurlaili Nurlaili (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
Menopause occurs exactly at the end of the last menstrual cycle, but the new certainty is obtained if a woman has not experienced the cycle for at least 12 months. When the levels of estrogen and progesterone decline, the hypothalamus and the pituitary gland trying to correct it and this leads to disruption of the normal operation of other body systems, including metabolism, brain chemistry, and bone conditions. The resulting changes include changes in the physical and psychological conditions are very individual (there are experienced and some not). Common physical changes experienced by menopausal women include: skin wrinkles or loosened, urinary incontinence (urinary control disorders), heart palpitations during activity, body temperature increases abruptly, headache, and easy to forget. While the changes in psychological conditions often lead to feelings of depression, and quick to anger. In addition it is the threat of osteoporosis (bone loss), which makes easy fractures impaired calcium absorption and poses a risk of cardiovascular disorders that contribute to raise the risk of heart disease and stroke.